TO THE PROBLEM OF ENVIRONMENTAL EDUCATION IN THE MODERN SCHOOL - Bilokonna, N.I.; Bilokonna, O.M. (Pedagogy of Higher and Secondary Education, 2008)
The article is devoted the questions of ecological education and his role in forming of personality of modern schoolboy.